Pertolongan Pertama Gigitan Binatang Rabies dan Edukasi Perawatan Luka Akibat Gigitan Binatang di Wilayah Kerja Puskesmas Medan Tuntungan, Kota Medan Tahun 2024 - Dewi Astuti Pasaribu; Elyani Sembiring; Martina Evlyn Romauli Hutahaean (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Rabies is an acute infectious disease of the central nervous system caused by the rabies virus and belongs to the zoonotic group, which is a disease that can be transmitted from animals to humans through bites or exposure from Rabies Transmitting Animals (HPR) such as dogs, monkeys, ferrets, cats, and wild animals that have been infected. In the prevention of rabies after exposure (Post Exposure Prophylaxis/PEP), there are three important elements, namely wound care, anti-rabies serum (SAR), and anti-rabies vaccine (VAR). This community service activity is carried out through approaches, preparation, and implementation with the aim of increasing the understanding of high school students about first aid and wound care due to the bite of an animal infected with rabies. The targets to be achieved in this activity include providing comprehensive health education about rabies, health risks for sufferers, rabies prevention, and how to treat wounds caused by rabies bites. With this education, it is hoped that students can have a better understanding and be able to apply first aid measures and wound care appropriately.